If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -6 * 2x = 24 Multiply -6 * 2 x + -12x = 24 Combine like terms: x + -12x = -11x -11x = 24 Solving -11x = 24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-11'. x = -2.181818182 Simplifying x = -2.181818182
| -2y+4=-14+8y | | -7x-32=x+13 | | -3(3y-7)-y=-3(y-5) | | 8.48x-2.6=-7.17x-7.1 | | h=55-20t-5t^2 | | -2y-7=15 | | 3/4(x-4)=2(x-1) | | -10v-10=9v-8 | | .25(n+2)=1 | | .40+.30(25-x)=.35(25) | | 8x-4x+2=x-4+6 | | 0.4(2c-30)=-0.8(c-4) | | x-6*2=24 | | (X+y+3z)-(4x-6y+z)= | | 90=w+w+(4w-6) | | 0.2(6c-48)=-0.6(c-2) | | 6y+2-y=8+4y-7 | | 2(n)=6-20 | | (2a+1)-a+2= | | 2t=5w-y | | -5x/520 | | 2t=5t-y | | 90=x+x-2 | | (X+y+4z)-(2x-6y+z)= | | 180=x+x+(x+3) | | 3/5m-5-1/2=1 | | 5/11a-3=16/11 | | 3/5m-5_1/2m=1 | | -2(x-7)=2(1+5x) | | -35/17=-49/34t | | 3x/7=.10 | | 3y/7=.10 |